Discovering the Role of Student Motivation in EFL Learning: A Bibliometric Analysis - Assholihy, Iffatus Sholicha; Rohmah, Zuliati (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This article presents a systematic review of students' motivation to learn English as a Foreign Language (EFL) over the past decade. The study examines publication trends, identifies relevant authors, analyzes article production from various countries and their collaborations, and explores commonly used keywords on this topic. Through bibliometric analysis, this research addresses gaps in previous studies, which predominantly focused on specific contexts or approaches. Instead, it provides broader findings that are not confined to certain settings. Data were collected from the Scopus database and analyzed with RStudio, which served as the primary tool for this study. Article selection adhered to the PRISMA guidelines, yielding 176 relevant articles published between 2014 and 2024. The findings indicate that research on student motivation in EFL learning has been consistently pursued over the past decade. This study also identifies an author from Indonesia as notable. Meanwhile, countries in the Middle East have produced the most publications and exhibit the highest collaboration on this topic. Additionally, the findings reveal that "learning" is the most frequently used term in research regarding student motivation in EFL learning.